Diatom valve counts from surface sediments from Young Sound fjord, North-East Greenland - Meri Marianne Mäkelä; Tiia Luostarinen; Sofia Ribeiro; Kaarina Weckström; Mikael K Sejr; Mie Hylstofte Sichlau Winding; Maija Heikkilä (PANGAEA, 2025)
Surface sediment samples collected from Young Sound fjord, Northeast Greenland, in 2013 or 2015. The surface sediment cores were collected as individual trips from small rubber boats using a Rumohr lot corer, multi corer or Kayak corer. Diatoms were counted and identified using a Zeiss Axio Imager.A2 upright research microscope with a Plan-Apochromat 100 exttimes/1.4 oil immersion objective, phase contrast optics and a total magnification of exttimes1000.
In: Mäkelä, MM et al. (2025): Diatom and dinoflagellate cysts determination from Young Sound fjord, North-East Greenland [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982994